Comparison of haematological parameters between alcoholics and non-alcoholics - ., Elanchezhian; T., Yoganandh; Mayilsamy, S.; Radhakrishnan, Shankar (International Journal of Research in Medical Sciences, 2017)
Background: Alcohol being one of the most commonly used drug, whose consequences include changes of CBC. The main causes leading to changes of CBC (complete blood count) are: myelosuppression that is accompanying with slight reduction in all blood cells, blood loss from gastrointestinal tract, malnutrition etc. Alcoholics may suffer from moderate anemia, characterized by enlarged, structurally abnormal RBC’s; mildly reduced numbers of WBC’s, especially of neutrophils; and moderately to severely reduced numbers of platelets. The objective of the study was to study the haematological manifestation among alcoholics based on the quantity and duration of alcohol intake and compare them with non-alcoholics. Methods: A cross-sectional study was conducted for a period of one year in our medical college hospital in medicine OPD with the collaboration of department of pathology and bio-chemistry. The study was started after getting the approval from the institutional ethical committee. A total of 150 study subjects were included in the study in which 50 were non-alcoholics, 50 were moderate alcoholics (less than or equal to two drinks per day for men and less than or equal to one drink per day for women) and the remaining 50 were severe alcoholics (more than 7 drinks a week in women and more than 14 drinks in a week in men). Blood investigations such as CBC, prothrombin time, liver function test, renal function test, folic acid levels and vitamin B12 levels were measured and the levels were compared between alcoholics and non-alcoholics. Results: Mean RBC count, mean MCH, MCHC were normal among the non-alcoholic group and it started decreasing among moderate alcoholics and more so with severe alcoholics and a similar type of result was also seen with total count and platelet count and the difference was found to be statistically significant. LFT, RFT, prothrombin time and vitamin B12 levels were found to be high and folate levels were decreased among alcoholics group when compared to non-alcoholics and the difference was statistically significant. Conclusions: Detection of hematological changes in chronic alcoholics and giving psychiatric counseling and treatment for alcohol dependence will decrease the future complications like cirrhosis liver, cardiac and renal disease, cerebellar degeneration, neuropathy, pancreatitis, etc. and reduce the morbidity and mortality in alcoholics.